Penguatan Partisipasi Politik Masyarakat Terdampak Bencana Galodo di Nagari Pasie Laweh Kabupaten Tanah Datar - Novi Budiman; Ulya Fitri; Mhd Alfajri Sukri; Mahmuda; Dewi Dahlan; Rita Handayani (Universitas Islam Negeri Siber Syekh Nurjati Cirebon, 2026)
Natural disasters not only cause physical and economic destruction but also disrupt civic engagement and political participation at the local level. However, limited scholarly attention has been given to how post-disaster political participation can be reconstructed through community-based and culturally grounded interventions. Drawing on political participation theory and the concept of political literacy, this study examines a Participatory Action Research (PAR) program conducted by lecturers and students of the Islamic Political Thought Study Program at UIN Mahmud Yunus Batusangkar in Nagari Pasie Laweh, Tanah Datar Regency, following the 2024 galodo disaster. The program implemented Focus Group Discussions (FGDs) with local stakeholders, political literacy training for women, and community-based anti–money politics campaigns ahead of the 2024 local elections. The findings reveal that participatory political education enhanced civic awareness, particularly among women and youth, revitalized local political discourse, and strengthened normative resistance to vote-buying practices. These outcomes indicate that community-based political literacy functions as a mechanism for post-disaster democratic recovery. The study proposes a contextual model of post-disaster political education that integrates participation, local cultural values, and democratic resilience, offering an adaptable framework for disaster-affected regions in strengthening local democracy.